Pendidikan Anti Korupsi sebagai Upaya Membangun Karakter Generasi Bangsa - Danu Fadliansyah Pratama; Rafie Sandy Zahran Siregar (GLOBAL SCIENTS PUBLISHER, 2026)
Corruption is a serious problem that hinders development and undermines social order in Indonesia. Anti-corruption education is a strategic solution to instill the values of honesty, responsibility, and integrity from an early age. This study aims to examine the importance of anti-corruption education in shaping the character of the younger generation and its implementation in the education system. The method used was a literature review, examining various relevant sources. The results of the study indicate that anti-corruption education is effective in building anti-corruption awareness and attitudes when implemented consistently in the curriculum and educational environment.